Mobile Phone and Family Happiness, Mediating Role of Marital Communication: An Attachment Theory Perspective - Akrim, A.; Dalle, Juhriyansyah (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Mobile phone communication has established itself as an essential element of people’s personal and working lives medium of connection in daily interactions and relationships. It has thus become significant for the most intimate form of interpersonal relations, including marital relationships. This small-scale research seeks to find the importance of mobile phone communication in marriage and its influence on family happiness. The study unearths the patterns of mobile phone communication among married partners, by outlining the most common reasons for communicating with the spouse on a mobile phone. In this research, a survey was conducted using a questionnaire to collect data from 30 respondents who were married partners, staff, or students in one of the state-owned universities in South Kalimantan. Each of the respondents possessed a mobile phone. The Mann-Whitney test indicates that the males profoundly believed that mobile phone communication was more important to their marriage than females to strengthen their relationship. Also, the males reported a higher frequency of sending messages and calling their spouses. By and large, the study results describe the most common reasons for communicating with the spouse. The outstanding reason is maintaining a strong intimate relationship by keeping in touch, sharing updates, emotions, feelings, knowing about children, and ensuring the safety of each other through checking on one another using a mobile phone. The findings have significance in showing the need for continued communication in a marital relationship, especially by using the fastest and most comfortable means of mobile phone. Given the synchronous nature of mobile phone communication, the results indicate that married spouses cannot do without it, especially in this Information Society, where we need updates from our spouses, children, friends, and the situation at large.